2022
DOI: 10.1002/cam4.4555
|View full text |Cite
|
Sign up to set email alerts
|

Patient, physician, and policy factors underlying variation in use of telemedicine for radiation oncology cancer care

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“… 2 It may be that their analyses were underpowered or that differences we found in rates of virtual visit participation between patient groups are driven less by patient preference and more by systemic factors such as those discussed in the following. To our knowledge this is one of the first reports looking at associations with virtual visit use in radiation oncology 22 ; our findings are supported by reports from general oncology 6 , 23 and non-oncology-specific investigations. 10 , 12 , 13 Furthermore, in an analysis of radiation therapy courses during COVID-19, De et al reported lower uptake among non-White patients and patients receiving shorter versus longer radiation therapy courses.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“… 2 It may be that their analyses were underpowered or that differences we found in rates of virtual visit participation between patient groups are driven less by patient preference and more by systemic factors such as those discussed in the following. To our knowledge this is one of the first reports looking at associations with virtual visit use in radiation oncology 22 ; our findings are supported by reports from general oncology 6 , 23 and non-oncology-specific investigations. 10 , 12 , 13 Furthermore, in an analysis of radiation therapy courses during COVID-19, De et al reported lower uptake among non-White patients and patients receiving shorter versus longer radiation therapy courses.…”
Section: Discussionsupporting
confidence: 86%
“… 10 , 12 , 13 Furthermore, in an analysis of radiation therapy courses during COVID-19, De et al reported lower uptake among non-White patients and patients receiving shorter versus longer radiation therapy courses. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In the post-peak period, the proportion of feasible visits conducted via telemedicine dropped significantly but was still 30%, well above the pre-pandemic baseline. This is consistent with national trends, in which the arrival of vaccines, relaxation of restrictions, improved safety measures, policy changes, and patient and clinician preferences influenced this shift back to traditional care delivery methods [1,[16][17][18][19][20]. In addition, as we hypothesized, the pandemic likely highlighted for many clinicians and patients numerous clinical contexts where remote care was suitable.…”
Section: Discussionsupporting
confidence: 79%
“… 2 , 6 Our recent study demonstrated that a majority of patients receiving radiation oncology care after the start of the COVID‐19 pandemic were managed through a hybrid telemedicine and in‐person management approach, and that utilization of telemedicine or in‐person management was almost equally influenced by patient‐level and physician‐level characteristics. 7 Therefore, using shared decisions between patients and their physicians to implement hybrid approaches may represent an advance toward fluidly integrating in‐person and telemedicine care to optimize the quality of clinical management and simultaneously promote patient‐centered care.…”
mentioning
confidence: 99%